Trends in Sport Sciences: formerly Studies in Physical Culture and Tourism 2018 Vol.25 No.1 (Akademia Wychowania Fizycznego w Poznaniu)
After years of concerns that nitrates present in the diet or water may cause cancer or birth defects, there are more and more reports inquiring that their consumption may, however, imply a number of health benefits. The impact of nitrates is related primarily to nitric oxide effects in individual cells and tissues. Double reduction, observed in NO3− → NO2− → NO metabolic pathway, provides an alternative way of nitric oxide production, especially in ischemic or hypoxic conditions, when its obtaining from L-arginine is limited. Studies have shown that nitrate-rich diet improves bacteriostatic activity and positively impacts the cardiovascular system by increasing peripheral circulation and lowering systemic blood pressure. The relationship between nitrate intake and improvement of gastric epithelial function, mitochondrial metabolism and exercise tolerance was also confirmed. Although results of recent studies seem optimistic it has to be considered that most of them were conducted in a very small research groups and not all gave unequivocal results. So, to reliably answer the title question one still have to wait for more comprehensive research projects’ results.